Specialty Addiction and Psychiatry Treatment Initiation and Engagement: Results from an SBIRT Randomized Trial in Pediatrics - Sterling, Stacy (J Subst Abuse Treat, 2017)
OBJECTIVE: Many adolescents needing specialty addiction or psychiatry treatment never access care. We examined initiation and engagement with addiction and/or psychiatry treatment among adolescents referred to treatment from a trial comparing two different modalities of delivering Screening, Brief Intervention and Referral to Treatment (SBIRT) to Usual Care in pediatric primary care. We hypothesized that both intervention arms would have higher initiation and engagement rates than usual care. METHODS: We randomized all pediatricians (n=52) in a pediatric primary care clinic to three arms: 1) pediatrician-only arm, in which pediatricians were trained to deliver SBIRT for substance use and/or mental health problems; 2) embedded-behavioral health clinician (embedded-BHC arm), in which pediatricians referred adolescents who endorsed substance use and/or mental health problems to a BHC; and 3) Usual Care (UC). We used electronic health record (EHR) data to examine specialty addiction and psychiatry treatment initiation and engagement rates after referral. RESULTS: Among patients who screened positive for substance use and/or mental health problems and were referred to specialty addiction and/or psychiatry (n=333), those in the embedded-BHC arm had almost four times higher odds of initiating treatment than those in the pediatrician-only arm, OR=3.99, 95% CI=[1.99-8.00]. Compared to UC, those in the pediatrician-only arm had lower odds of treatment initiation (OR=0.53, 95% CI=[0.28-0.99]), while patients in the embedded-BHC arm had marginally higher odds (OR=1.83, 95% CI=[0.99-3.38]). Black patients and those with other/unknown race/ethnicity had lower odds of treatment initiation compared with white adolescents; there were no gender or age differences. We found no differences in treatment engagement across the three arms. CONCLUSIONS: Embedded BHCs can have a significant positive impact on facilitating treatment initiation for pediatric primary care adolescents referred to addiction and/or psychiatry services.